Terrain morphometric characteristics as indicators of Ukrainian Roztochia springs localization - Іванович, Богдан (Київський національний університет імені Тараса Шевченка, 2019)
Розкриття водоносних горизонтів ерозійними врізами є одним із основних факторів утворення джерел, тому аналіз морфометричних показників території, де локалізуються джерела, необхідний для розуміння умов їх формування. За допомогою засобів ГІС побудовано карти вертикального, горизонтального розчленування, крутості земної поверхні та отримано інформацію про морфометричні характеристики рельєфу у місцях локалізації джерел та території ландшафтів Українського Розточчя. Підтверджено зв’язки між локалізацією джерел та морфометричними показниками рельєфу. Встановлено нерівнозначність різних морфометричних параметрів як індикаторів поширення джерел. Виявлено нерівномірність кореляції морфометричних характеристик рельєфу та локалізації джерел, а також умови, за яких вони корелюються найкраще.

The opening of aquifers with erosional downcut is one of the main factors in springs occurrence, therefore, morphometric analysis of the territory where springs are localized is necessary to understand conditions of their formation. Maps of vertical and horizontal relief dissection and steepness of land surface were created using GIS and the data about terrain morphometric characteristics in the places of springs localization were obtained, as well as for the territory of the Ukrainian Roztochia landscapes. More than 75% of the Ukrainian Roztochia springs, confined (maximum steepness of slopes within a radius of 250 m) to steep and very steep slopes and high vertical dissection of more than 60 m/km2, are attributed to 38.32% of spring localization spots. The link between springs localization and terrain morphometric indicators has been confirmed. It involves the similarities between landscape areas and springs localization spots morphometrics in general and on the each landscape particularly, direct matching between terrain morphometric parameters and springs quantity in landscapes, certain springs associations with steep and very steep slopes and places with high values of vertical dissection. Moreover, the abovementioned shows inequivalence of various morphometric characteristics as indicators of springs distribution. In general, terrain morphometrics and springs localization correlated unevenly. Morphometric characteristics of the relief, as the springs localization indicators best illustrate the situation in the Dubrovytskyi landscape (it has the higher values of dissection deepness, density and the steepness of land surface), also it explains non-availability of springs in the Domazhyrskyi landscape. Morphometric values are significantly lower than in other landscapes, what is low favourable for springs formation. This evidences that the particularly well-defined influence of terrain morphometrics on springs distribution occurs in conditions of more homogeneous strongly or slightly dissected nature of the terrain.
Морфометричні характеристики рельєфу як індикатори локалізації джерел Українського Розточчя
Keywords: Groundwater springs; landscape; vertical relief dissection; horizontal relief dissection; steepness of land surface; Ukrainian Roztochia; джерела підземних вод; ландшафт; вертикальне розчленування; горизонтальне розчленування; крутість земної поверхні; Українське Розточчя